Pendampingan Gerakan Literasi Sekolah Dalam Pembelajaran Di Sekolah Dasar - Subhananto, Aprian; Helminsyah, Helminsyah; Sari, Mira Dahlia; Is, Zulheri; Wahyuni, Rita (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
This activity is referred to as assisting the School Literacy Movement (GLS) in learning in elementary schools. GLS assistance is an important aspect to increase students' interest in reading through literacy activities at school. The method applied in this service is assistance in implementing GLS, with SDN 2 Banda Aceh teachers as the main target. This assistance consists of four sessions, where at the first meeting there is counseling about the effectiveness of the school literacy movement with a time allocation of 2-3 credits, and the 2nd to 4th sessions involve monitoring the implementation of GLS at SDN 2 Banda Aceh with a time allocation of 3-4 credits. SKS. The results achieved involve the habit of reading for 15 minutes before class time, organizing the library, creating an environment rich in texts through the installation of slogans and posters, as well as setting up the classroom which provides text diversity and comfort for students in the learning process.